INTEGRATING CRIMINAL LAW ENFORCEMENT AND THE CIVIL VALIDITY OF SMART CONTRACTS: A LEGAL ANALYSIS OF CRYPTO-ASSET-BASED SCAMMING CRIMES IN INDONESIA - Bambang Julianto; Rabith Madah Khulaili Harsya; Andi Mohammad Galib; Dani Amran Hakim; Aklima (ITB AAS Indonesia Surakarta, 2026)
The evolution of blockchain technology has introduced smart contracts as autonomous and immutable digital transaction instruments. However, these technical characteristics create legal ambivalence when used as a means of fraudulent acts based on crypto assets. This study aims to analyze the integration of criminal law enforcement and the civil validity of smart contracts in the context of crypto crimes in Indonesia. Using normative legal research methods and a comparative approach, this study finds a legal gap in determining the civil status of contracts born of malicious intent (mens rea). The analysis shows that although smart contracts are technically valid in blockchain systems, they can be invalidated under civil law if proven to contain elements of fraud. This study recommends the need for regulatory synchronization between the ITE Law, the National Criminal Code, and civil contract law to provide comprehensive legal protection for crypto asset investors in Indonesia